Preface (OCL 2011 Proceedings) - Cabot, Jordi; Clarisó, Robert; Gogolla, Martin; Wolff, Burkhart (Electronic Communications of the EASST, 2011)
This preface reports on the 11th workshop on OCL and Textual Modelling held at the TOOLS Federated Conferences in 2011. The workshop focused on the current state of OCL (standard, tool support, adoption, ...) and the application of textual modelling to different domains. The workshop included presentationstogether with a discussion session. All the workshop materials are available at http://gres.uoc.edu/OCL2011.